Why and How Political Science Can Contribute to Public Health? Proposals for Collaborative Research Avenues - France Gagnon; Pierre Bergeron; Carole Clavier; Patrick Fafard; Elisabeth Martin; Chantal Blouin (Kerman University of Medical Sciences, 2017)
Written by a group of political science researchers, this commentary focuses on the contributions of political science to public health and proposes research avenues to increase those contributions. Despite progress, the links between researchers from these two fields develop only slowly. Divergences between the approach of political science to public policy and the expectations that public health can have about the role of political science, are often seen as an obstacle to collaboration between experts in these two areas. Thus, promising and practical research avenues are proposed along with strategies to strengthen and develop them. Considering the interdisciplinary and intersectoral nature of population health, it is important to create a critical mass of researchers interested in the health of populations and in healthy public policy that can thrive working at the junction of political science and public health.